2014
DOI: 10.1021/jp501453m
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies of Complex Silver–Magnetite Nanoheterodimers with Controlled Morphology

Abstract: This work discusses the influence of synthesis conditions on self-assembly capability and morphology of obtained Ag–Fe3O4 nanoheterostructures. Samples were synthesized in two steps: first silver nanoparticles were synthesized and then used as seeds for the growth of iron oxide nanoparticles in a second step. The silver nanoparticle size was tuned, changing the oleylamine (OAm) and oleic acid (OA) ratio, which enables us to study the influence of chemical agents and seed size on the final magnetic nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…To expand the discussion regarding the factors that involved the growing of these nanostructures, the surface charges associated with the active sites of the nanoparticles should be considered [18]. Based on the fact that the particle size and structure type determine the compensation charge in the nanoparticles surface, it can be deduced that mainly the size of decahedral Ag nanoparticles would influence the charge compensation and hence the formation of Fe 2 O 3 heterostructures [24], due the fact that the decahedral nanoparticles exhibit greater reactivity. In this regard, some studies have reported these structures as a function of the -Fe 2 O 3 size/size Ag seed ratio [22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To expand the discussion regarding the factors that involved the growing of these nanostructures, the surface charges associated with the active sites of the nanoparticles should be considered [18]. Based on the fact that the particle size and structure type determine the compensation charge in the nanoparticles surface, it can be deduced that mainly the size of decahedral Ag nanoparticles would influence the charge compensation and hence the formation of Fe 2 O 3 heterostructures [24], due the fact that the decahedral nanoparticles exhibit greater reactivity. In this regard, some studies have reported these structures as a function of the -Fe 2 O 3 size/size Ag seed ratio [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight the synthesis methodology presented in this research since it offers a simple route for obtaining controlled bimetallic nanostructures. This synthesis is carried out at room temperature while some other methodologies involve temperature (∼400 ∘ C) [22,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…one of the most abundant oxides, magnetite Fe3O4, whereas Ag has a four times higher extinction coefficient than Au at the surface plasmon resonance [13]. The extremely high affinity of iron towards oxidation has, however, hindered the fabrication of purely metallic FeAg nanoparticles and most studies are focused on the fabrication and study of particles combining silver with iron oxides [9,14] as well as their applications in e.g. biomedicine [15], theranostics [16], SERS [17], catalysis and imaging [18].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis consists on a decomposition of an organometallic precursor in presence of surfactants [22]. Silver-magnetite dimer synthesis was carried out using the same synthesis method on previously formed Ag seed colloid solution, as described in [22][23][24][25]. The shape of the heating curve of this two-step process can be seen in Figure 1-b.…”
Section: A Synthesismentioning
confidence: 99%
“…Typical relationship between size and geometry is observed: for smaller diameters, NPs tend to be more spherical in order to minimize their surface energy. On the other hand, nanoparticles of larger sizes can have different shapes, such as cubes, parallelepipeds or hexagons [25].…”
Section: A Synthesismentioning
confidence: 99%